If Physicians “Don’t Ask” and LGBT Patients “Don’t Tell,” Then Who’s Talking ?: Educational Strategies for Addressing Health Care Disparities Facing LGBT Patients - Dana Dudzinska-Przesmitzki; Matthew A. Eichler (Adult Education Research Conference, 2010)
Numerous disparities exist in the provision of health services to LGBT people. The utilization of theoretical-grounded and empirically- tested adult educational strategies (e.g., deliberate practice and concept mapping) within medical education may improve the quality of health services offered to LGBT people.